Estratégia para a incorporação de impactes ambientais, sociais e económicos específicos num métdo de avaliação da sustentabilidade de edifícios de saúde (HBSA Método) - Castro, Maria de Fátima Morais de Aguiar e (2016)
The design of a hospital environment involves many concerns related to the satisfaction and well-being of the medical personnel, patients, and administrators, and at the same time requires strong social responsibility and has a high impact on a city. Currently, it seems that the majority of this type of building is not designed or used in a sustainable way, although some tools have already been developed to support decision-making to optimize building sustainability. Based on this context, the aim of this article is to discuss the barriers to the dissemination of sustainable practices in healthcare buildings, and to propose the structure of a methodology that facilitates the incorporation of sustainability principles during the different life-cycle stages of a hospital building while overcoming some of the identified barriers. The structure presented is oriented to the Portuguese context and is based on the work done to date by the ISO and CEN organizations and other international sustainability assessment schemes already available on the market.